2012
DOI: 10.3390/molecules171012121
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki-Miyaura Reactions Catalyzed by C2-Symmetric Pd-Multi-Dentate N-Heterocyclic Carbene Complexes

Abstract: Suzuki-Miyaura coupling reactions are promoted by Pd complexes ligated with C2-symmetric multi-dentate N-heterocyclic carbenes derived in situ from Pd(OAc)2 and imidazolium salts. Good to excellent yields were obtained for aryl bromides as substrates. Turnover numbers of up to 105 could be achieved with 5 × 10−4 mol% of Pd(OAc)2/1 × 10−3 mol% NHC precatalyst in 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In other reports, the authors mentioned that unidentified structures were detected in some catalytic reactions. 11 We also observed the undesired product and we found that this occurs when using aqueous solvents. In aqueous solvents, the benzoyl chloride converts the benzoic acid and thus directly affects the reaction efficiency.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In other reports, the authors mentioned that unidentified structures were detected in some catalytic reactions. 11 We also observed the undesired product and we found that this occurs when using aqueous solvents. In aqueous solvents, the benzoyl chloride converts the benzoic acid and thus directly affects the reaction efficiency.…”
Section: Resultsmentioning
confidence: 61%
“… 10 They control metal ions by blocking the reactive sites of the metal ion and preventing them from entering into their normal (and in many cases undesirable) reactions. As coordination flexibility in hybrid ligands can have a profound effect on catalytic performance, 11 we were interested in effect of NHC structure and nitrile group on catalytic activities. So, the azolium salts (benzothiazolium, benzimidazolium, imidazolium) containing 2-nitrile substituted benzyl groups and not nitrile group were prepared.…”
Section: Introductionmentioning
confidence: 99%